A narrative review of Asian female travellers: looking into the future through the past. Issue 10 (27th July 2017) - Yang, Elaine Chiao Ling; Khoo-Lattimore, Catheryn; Arcodia, Charles
Abstract : Following the rise of tourism in Asia, a growing female travel market has been observed in the region. Nevertheless, limited research has considered the travel experience of Asian women. In response to the dearth of research on Asian female travellers, this study employs a narrative synthesis approach through a postcolonial feminist lens to review the extant literature on Asian female travellers, with the aim to contribute to a cultural understanding of the historical and contemporary travel practices of Asian women. Based on this review, it is evident that Asian women's travel behaviour is influenced by cultural identities and gender stereotypes. However, existing literature has also demonstrated the agency of Asian women in resisting discriminatory gender practices in tourism, which is represented in the transformation of the identity of Asian female travellers. Accordingly, an agenda for future research is proposed and some implications for the industry are discussed. This study addresses the western-centric and androcentric criticisms in tourism field and provides an alternative reading of women's travel behaviour from an Asian perspective. This study has contributed to the critical tourism scholarship in Asia and has built an important foundation for future research on Asian female travellers, an area that is not well investigated.